Analysis Satisfaction Patient Treat Inap In dr. Saragih Djasamen Hospital Pematang Siantar - Riada Marenny Pasaribu (PT Inovasi Pratama Internasional, 2022)
Service health is wrong one factor which influence degrees health Public. Provider service health like house sick on era modern this must improve the quality of public health services. In maintenance, good government hospitals and private hospitals have a quality management component to meet patient satisfaction with health services provided by the hospital. Destination from study this is for knowing satisfaction patient to service in RSUD Dr. Djasamen Saragih Pematang Siantar. This research is classified as observational research and is study quantitative descriptive with design studies cross sectional . Sample study This is as many as 97 patients. Data collection is done by distributing questionnaires and conduct interviews with respondents, namely patients or families of patients who are in the hospital inpatient room B. Analysis of research data using a computer system that is Microsoft Excel 2013. Results study show that score index satisfaction Public that is as big as 77,851, where number the there is on range 76.61 – 88.30 which show quality service B or good. Hospitals need to conduct a patient satisfaction survey every month or once every three months on a regular basis, in order to know the level of community satisfaction and could made ingredient evaluation for house sick if there is patient which not enough satisfied.